2007
DOI: 10.1111/j.1538-7836.2007.02530.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a U‐shaped association between factor XII activity and overall survival

Abstract: Summary. Introduction:The clinical relevance of decreased coagulation factor XII (FXII) plasma activity as a risk factor for both venous and arterial thrombosis is still discussed controversially. The current study evaluated the predictive value of FXII levels for all-cause mortality in a large Viennese patient cohort. Patients and methods: Individuals, whose FXII activity levels were determined for suspected coagulation disorders or thrombophilia screening between 1991-2003 were included in this study (n = 89… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 23 publications
3
73
2
3
Order By: Relevance
“…However, a FXII activity rate below 10% does not increase mortality rates, thus resulting in a U-shaped survival curve. 27 Larger epidemiological studies in the Netherlands and Switzerland did not find a correlation between FXII deficiency and increased thrombotic risk. 28,29 Patients with severe deficiency of factor XI, the substrate for activated FXII, have a reduced incidence of DVT.…”
Section: The Vessel Wall and Coagulationmentioning
confidence: 99%
“…However, a FXII activity rate below 10% does not increase mortality rates, thus resulting in a U-shaped survival curve. 27 Larger epidemiological studies in the Netherlands and Switzerland did not find a correlation between FXII deficiency and increased thrombotic risk. 28,29 Patients with severe deficiency of factor XI, the substrate for activated FXII, have a reduced incidence of DVT.…”
Section: The Vessel Wall and Coagulationmentioning
confidence: 99%
“…Interestingly, however, the group with fXII:c levels Ͻ10% (n ϭ 58) demonstrated no increased mortality, resulting in a U-shaped survival curve. 15 The reason for the increased mortality in moderate-deficiency patients could not be determined because the relationship held true for noncancer mortality, all-cause vascular mortality, and mortality due to ischemic heart disease.…”
Section: Relevance Of Animal Data To Humansmentioning
confidence: 99%
“…These questions would require further verification. A clear correlation between FXII and thrombosis and inflammation has not yet been established, and some studies have demonstrated a "U" shaped correlation between plasma FXII concentration and mortality of various reasons [34], suggesting that partial inhibition of FXII may actually increase mortality. Complete or nearly complete inhibition of FXII/FXIIa is difficult to achieve, bringing extra obstacles to development of therapeutic FXII/FXIIa inhibitor.…”
Section: Discussionmentioning
confidence: 99%